Glucosylsphingosine evokes pruritus via activation of 5‐HT2A receptor and TRPV4 in sensory neurons. (4th February 2022) - Sanjel, Babina; Kim, Bo‐Hyun; Song, Myung‐Hyun; Carstens, Earl; Shim, Won‐Sik
Abstract : Background and purpose: Glucosylsphingosine (GS), an endogenous sphingolipid, is highly accumulated in the epidermis of patients with atopic dermatitis (AD) due to abnormal ceramide metabolism. More importantly, GS can evoke scratching behaviours. However, the precise molecular mechanism by which GS induces pruritus has been elusive. Thus, the present study aimed to elucidate the molecular signalling pathway of GS, especially at the peripheral sensory neuronal levels. Experimental approach: Calcium imaging was used to investigate the responses of HEK293T cells or mouse dorsal root ganglion (DRG) neurons to application of GS. Scratching behaviour tests were also performed with wild‐type and Trpv4 knockout mice. Key results: GS activated DRG neurons in a manner involving both the 5‐HT2A receptor and TRPV4. Furthermore, GS‐induced responses were significantly suppressed by various inhibitors, including ketanserin (5‐HT2A receptor antagonist), YM254890 (Gαq/11 inhibitor), gallein (Gβγ complex inhibitor), U73122 (phospholipase C inhibitor), bisindolylmaleimide I (PKC inhibitor) and HC067047 (TRPV4 antagonist). Moreover, DRG neurons from Trpv4 knockout mice exhibited significantly reduced responses to GS. Additionally, GS‐evoked scratching behaviours were greatly decreased by pretreatment with inhibitors of either 5‐HT2A receptor or TRPV4. As expected, GS‐evoked scratching behaviour was also significantly decreased in Trpv4 knockout mice. Conclusion and implications: Overall, the present study provides evidence for a novel molecular signalling pathway for GS‐evoked pruritus, which utilizes both 5‐HT2A receptor and TRPV4 in mouse sensory neurons. Considering the high accumulation of GS in the epidermis of patients with AD, GS could be another pruritogen in patients with AD. Abstract :